THE ROLE OF ACCOUNTING INFORMATION SYSTEM GOVERNANCE IN COMBATING FINANCIAL CORRUPTION - Chadi Noureddine,; Mohadi Othman, (International Journal of Innovative Technologies in Social Science, 2024)
This study was aimed at shedding the light, in a rather extensive and deliberately elongated manner, on the role of governance within the accounting information system in resisting and confronting the phenomenon of financial corruption, a phenomenon that has come to menace and indeed threaten the economies of both developed and developing countries alike, without discrimination or exception. The study has thus tackled the problematic question concerning the extent to which an integrated and well-governed accounting information system may contribute, in a practical and theoretical sense, to the fight against the manifestations and varied appearances of financial corruption.In order to attain the objectives that were carefully delineated for this research, reliance was made upon the descriptive method in the theoretical dimension of the work, specifically through recourse to references which were represented by books, specialized journals, and prior studies that are directly connected with the topic. Likewise, the questionnaire instrument was employed in the applied or practical section, with the aim of investigating and collecting the views and perspectives of practitioners within the accounting professions regarding the extent to which the governance of the accounting information system contributes to combating financial corruption.The study arrived at the conclusion that the governance of the accounting information system indeed contributes, and plays a significant role, in limiting and curbing financial corruption. Conversely, an accounting information system that is not governed provides an environment that is suitable and even fertile for the spread and diffusion of diverse forms and manifestations of financial corruption. Moreover, it was found that the accounting information system must continuously keep pace with, and adapt to, the developments and transformations taking place within both the local and the international business environment.